Holistic Word Processing Is Involved in Fast Parallel Reading - Ventura, Paulo (2019)
Holistic processing of words has been previously observed. When readers have to decide whether the target part of a study and test words are the same, their performance is affected by the irrelevant part. The goal of the present study was to provide an empirical test of the idea that holistic word processing is involved in expert reading (fast and parallel letter reading pattern) by exploring the perceptual expertise limits of the neuronal systems dedicated to reading. We presented adult readers with words in the composite paradigm that were degraded by word rotation (22.5º and 67.5º). Rotations were applied clockwise or counterclockwise. A word rotation of 22.5º is below the threshold of the perceptual expertise of the Visual Word Form (VWF) System, while a rotation of 67.5º is above the threshold of the perceptual expertise of the VWF system. The word composite effect was found only for a degree of rotation within the field of expertise of the ventral visual system, thus within the limits for fast, parallelletter reading. We thus showed that word holistic processing occurs within the functional, fast, and parallel reading route.